Response of foraminiferal faunas to paleoceanographic changes in the Gulf of Guinea from the late Paleocene to the Initial Eocene Thermal Maximum (IETM) - Gebhardt, Holger; Adekeye, Olabisi; Bankole, Samson (Anuário do Instituto de Geociências, 2006)
Abstract